An Analysis of Conjunctions Found in Barack Obama’s Farewell Speech Text - Sulistyaningsih Sulistyaningsih; Joko Slamet (OKARA: Jurnal Bahasa dan Sastra, 2018)
In communication people use conjunctions in their speech, so did Barack Obama in his farewell speech. His speech consists of many various conjunctions that will be interesting to study to understand the connection between the sentences delivered by Him. The purpose of this study is to find out types of conjunction especially external conjunction, internal conjunction, and continuatives in Barack Obama’s farewell speech text based on semantics naming. It used the descriptive qualitative method. The instruments were researchers themselves, table, Barack Obama’s speech text. The data collection were taken from were taken from the internet, it was the President of the United State of America (period: 2009-2017) Barack Obama's speech text of his farewell in Chicago. To analyze all data, this study used the theory of conjunction by Martin and Rose (2007). The data were identified types of conjunction, then were classified, were displayed, and were described. The finding out of words that were analyzed conjunctions and continuatives were 18 (eighteen) types of external conjunctions, 8 (eight) types of internal conjunctions and 3 (three) continuatives.